Light‐Field Imaging and Display Systems. Issue 4 (1st July 2016) - Balram, Nikhil; Tošić, Ivana
Abstract : Light‐field imaging and display are often treated as separate areas, but at a conceptual level they are closely related. Display can be viewed as the reverse path of imaging, and this way of thinking can be helpful in the design of either type of system. This article offers a brief outline of both light‐field imaging and display systems and a roadmap for their practical use going forward.